Pengukuran Risiko dan Mitigasi Risiko Menggunakan HOR (House Of Risk) Pada Industri Pengolahan Buah Pisang : Risk Measurement and Risk Mitigation Using HOR (House Of Risk) in Banana Fruit Processing Industry - Andanu, Odi; Sangadah, Hanik Atus; Wulandari, Sri; Putri, Fina Pradika (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2024)
Banana fruit is one type of fruit that grows well in the tropics. The total production of bananas has increased by 6.85% from 2020 to 2021. There are various potential industries that process banana derivative products, including banana chips in Kepahiyang Regency, Bengkulu. The relatively rapid development of banana chip SMEs is the basis for the need for research related to risk mitigation that may arise in the industry. Research data analysis was carried out using the House of Risk (HOR) method. The results of this study show that 22 risk sources and 14 risk mitigation alternatives are identified in the banana chips industry. From the results of the analysis, it is hoped that several risk mitigation alternatives that can be applied by the banana chips industry will be obtained. The results of the Effectiveness to Difficulty (ETD) rating obtained 3 top ranking results from risk mitigation, namely preparing and providing training for employees (M3) with a value of 20759.25, making planning and controlling raw material inventories more accurate (M10) with a value of 19866, and making and implementing good and correct banana chip production SOP (M4) with a score of 17726.